Abandoned stone powder composite fly ash concrete in alpine region

By using waste stone powder and composite gas inductors in concrete in high-altitude areas, the problem of insufficient freezing resistance of traditional concrete is solved, and higher freezing resistance and longer service life are achieved, while reducing the accumulation of waste stone powder and environmental pollution.

CN119613022APending Publication Date: 2025-03-14SHAANXI HENGSHENG GREEN CONSTRUCTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411743646.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The lack of freezing resistance of traditional concrete in high-altitude areas has led to reduced load-bearing capacity and durability of infrastructure during freeze-thaw damage.

Method used

Use waste stone powder composite fly ash concrete in high-altitude areas. By adding waste stone powder and adjusting raw material components, pores are introduced using composite gas induction agent and filled with waste stone powder to reduce pore size and improve the frost resistance of concrete.

Benefits of technology

It significantly improves the freezing resistance of concrete, avoids freeze-thaw damage, extends the service life of the structure, and reduces the accumulation of waste stone powder and environmental pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses waste stone powder composite fly ash concrete suitable for alpine regions. The concrete is prepared from the following components in parts by weight: 63 to 85 parts of fly ash, 120 to 140 parts of cement, 3.9 to 5.0 parts of polycarboxylic acid high-performance water reducing agent, 130 to 150 parts of waste stone powder, 235 to 265 parts of medium sand, 510 to 520 parts of gravel, 73 to 79 parts of water and 0.08 to 0.1 part of composite air entraining agent. By adding the waste stone powder and adjusting the raw material components of the concrete, internal pores of the concrete can be controlled, while a large number of pores are introduced into the composite air entraining agent, the pores are filled with the waste stone powder, the pore diameter of the pores is reduced, a certain number of small pores are formed in the concrete, and then the anti-freezing performance of the concrete is improved; the invention is applicable to the technical field of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a fly ash composite concrete made of waste stone powder in high-cold areas. Background Art

[0002] As an indispensable artificial building material, concrete plays a vital role in the development of the construction field. However, the traditional concrete industry is struggling due to the consumption of non-renewable resources such as natural sand and gravel and the environmental pollution caused by the cement production process.

[0003] In order to make up for the lack of sustainable development potential of traditional concrete, the existing technology recycles construction waste into aggregate to prepare recycled aggregate concrete for structure; on the other hand, waste stone powder is used as a mineral admixture to replace cementitious materials to save the amount of cement and admixtures, and at the same time it can also solve the problem of land occupation and environmental pollution caused by waste stone powder.

[0004] However, due to the high water absorption rate of waste stone powder, the consistency of concrete increases rapidly after adding it, and a large amount of water is needed to ensure the pumping performance of concrete; at the same time, the addition of a large amount of water greatly increases the water-cement ratio, seriously affecting the strength of concrete. Since there are a large number of high-altitude cold areas in my country, the region has high requirements for the antifreeze performance of service concrete to avoid the reduction of bearing capacity and durability of infrastructure such as railway projects due to freeze-thaw damage, and the threat to structural safety. If waste stone powder can be used to prepare antifreeze concrete, a large amount of waste stone powder can be consumed.

[0005] Therefore, how to add waste stone powder into frost-resistant concrete is an issue that researchers urgently need to solve. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a waste stone powder composite fly ash concrete for high-cold areas. The concrete can control the internal pores of the concrete by adding waste stone powder and adjusting the raw material components of the concrete. While the composite air entraining agent introduces a large number of pores, the waste stone powder is used to fill the pores, reduce the pore diameter, and make the concrete have a fine pore diameter, thereby improving the antifreeze performance of the concrete, and solving the problem of how to add waste stone powder to antifreeze concrete.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a waste stone powder composite fly ash concrete in high-cold areas, characterized in that the concrete comprises the following components in parts by weight: 63-85 parts of fly ash, 120-140 parts of cement, 3.9-5.0 parts of polycarboxylic acid high-performance water reducer, 130-150 parts of waste stone powder, 235-265 parts of medium sand, 510-520 parts of crushed stone, 73-79 parts of water, and 0.08-0.1 parts of composite air entraining agent.

[0008] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the composite air-entraining agent includes the following components in parts by weight: 5 to 12 parts of sulfuric acid, 50 to 70 parts of rosin powder, 4 to 15 parts of bisphenol, and 10 to 15 parts of sodium hydroxide, and the mass concentration of sulfuric acid is 20% to 40%.

[0009] The composite air entraining agent prepared by the invention adopts sulfuric acid, rosin powder, bisphenol and sodium hydroxide as raw materials and has the characteristics of simple preparation process, short preparation cycle and low preparation cost.

[0010] The above-mentioned waste stone powder composite fly ash concrete suitable for high-cold areas is characterized in that the preparation method of the concrete includes the following steps:

[0011] Step 1: Put rosin powder with a particle size of no more than 0.4 mm, sulfuric acid and bisphenol into a reaction kettle, and stir at 60° C. to 80° C. for more than 4 hours to obtain a mixture;

[0012] Step 2: Place the NaOH solution in the mixture obtained in step 1, stir at 80° C. to 90° C. for 3 hours, and then pour the mixture into a container to obtain a composite air-entraining agent;

[0013] Step 3: Weigh the waste stone powder, medium sand and crushed stone according to the mix ratio and mix them evenly to obtain mixed aggregate;

[0014] Step 4: Weigh fly ash, cement, polycarboxylic acid high-performance water-reducing agent, water and the composite air-entraining agent obtained in step 2 according to the mix ratio, and then add them to the mixed aggregate obtained in step 3 and stir to obtain concrete.

[0015] The present invention evenly mixes aggregate components that account for most of the mass of the raw materials first, so that concrete can be stirred in a relatively short time, thereby avoiding concrete segregation caused by too long stirring time.

[0016] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the fineness modulus of the waste stone powder is 2.0-2.5, and the methylene blue of the waste stone powder is less than 1.3.

[0017] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the waste stone powder includes modified waste stone powder, and the preparation method of the modified waste stone powder is: the waste stone powder is dried and placed in an alcohol solution for ultrasonic dispersion for more than 2 hours to obtain a suspension; the silane coupling agent KH-570 is added to a mixed solution of anhydrous ethanol and oxalic acid and stirred, and then poured into the suspension, stirred at 75°C to 80°C, and then centrifuged and dried to obtain the modified waste stone powder.

[0018] The present invention uses a silane coupling agent to modify the waste stone powder, so that the organic functional groups of the silane coupling agent are chemically bonded to the surface of the modified waste stone powder, which can reduce the degree of agglomeration of the waste stone powder particles, so that the modified waste stone powder can be evenly dispersed in the mixed aggregate, and the water absorption rate is improved, thereby making the concrete pumpable under the condition of a small water-binder ratio; at this time, the tiny pores and defects on the surface of the modified waste stone powder can absorb a small amount of water, which is gradually released during the curing and hardening process of the concrete, so that the long-term strength of the concrete is improved; in addition, the uniform dispersion of the modified waste stone powder can further improve the filling effect of the pores inside the concrete.

[0019] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the volume ratio of anhydrous ethanol and oxalic acid in the mixed solution is 1:1.

[0020] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the water reduction rate of the polycarboxylic acid high-performance water reducing agent is 20% to 25%.

[0021] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the particle size of the fly ash is 1.0mm to 3.0mm

[0022] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the fineness modulus of the medium sand is 2.4-2.7.

[0023] The invention adopts medium sand with a fineness modulus of 2.4 to 2.7, which can be mixed with waste stone powder and crushed stone to obtain better particle gradation, improve the density of concrete, and further improve the compressive strength of concrete; in addition, the medium sand with the fineness modulus has good stability and low cost.

[0024] The above-mentioned one is suitable for waste stone powder composite fly ash concrete in high-cold areas, characterized in that the particle size of the crushed stone is 5mm to 25mm.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. The present invention can control the internal pores of concrete by adding waste stone powder and adjusting the raw material components of concrete. While the composite air-entraining agent introduces a large number of pores, the waste stone powder is used to fill the pores to reduce the pore diameter, so that the concrete has a small pore diameter, thereby improving the antifreeze performance of the concrete.

[0027] 2. The waste stone powder added to the concrete of the present invention can replace medium sand, optimize the gradation of mixed aggregates and reduce the production cost of concrete; in addition, the high water absorption of the waste stone powder can improve the water retention of concrete and avoid segregation during concrete transportation or pumping.

[0028] 3. The present invention uses waste stone powder as the raw material for concrete, which can reuse solid waste and greatly reduce the accumulation of waste stone powder. In addition, it replaces a part of the medium sand, which can avoid the energy consumption and carbon emissions of preparing this part of machine-made sand or excavating river sand, and is conducive to the green development of the construction industry.

[0029] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0030] Example 1

[0031] The concrete of this embodiment includes the following components in parts by weight: 85 parts of fly ash, 120 parts of cement, 3.9 parts of polycarboxylic acid high-performance water-reducing agent, 150 parts of waste stone powder, 245 parts of medium sand, 516 parts of crushed stone, 75 parts of water, and 0.08 parts of composite air-entraining agent.

[0032] The method for preparing concrete in this embodiment comprises the following steps:

[0033] Step 1: Add 60 parts of rosin powder with a particle size of 0.6 mm, 6 parts of sulfuric acid and 10 parts of bisphenol into a reaction kettle, and stir at 70° C. for 4 hours to obtain a mixture; the mass concentration of the sulfuric acid is 30%;

[0034] Step 2: Add 10 parts of NaOH solution to the mixture obtained in step 1, stir at 85° C. for 3 hours, and then pour into a container to obtain a composite air-entraining agent;

[0035] Step 3: Evenly mix 150 parts of waste stone powder, 245 parts of medium sand, and 516 parts of crushed stone to obtain a mixed aggregate; the fineness modulus of the medium sand is 2.7, and the particle size of the crushed stone is 5 mm to 25 mm;

[0036] Step 4: Add 85 parts of fly ash, 120 parts of cement, 3.9 parts of polycarboxylic acid high-performance water-reducing agent, 75 parts of water and 0.08 parts of the composite air-entraining agent obtained in step 2 to the mixed aggregate obtained in step 3, and stir for 3 minutes at a speed of 55 r / min to obtain concrete; the fly ash particle size is 1.0 mm to 3.0 mm, and the water reduction rate of the polycarboxylic acid high-performance water-reducing agent is 20%.

[0037] The concrete prepared in this embodiment was loaded into test molds of 150mm×150mm×150mm and 100mm×100mm×400mm, compacted by tamping, and demolded after hardening and setting to obtain concrete specimens; after testing, the 7d compressive strength of the 150mm×150mm×150mm concrete specimen was 30.7MPa, and the 28d compressive strength was 45.2MPa; a freeze-thaw cycle test was performed on a 28d 100mm×100mm×400mm concrete specimen, and when the number of cycles reached 200, its relative dynamic elastic modulus did not decrease to 60% of the relative dynamic elastic modulus of the blank control group (a 28d 100mm×100mm×400mm concrete specimen that was not subjected to a freeze-thaw cycle test), and the mass loss rate was less than 5%.

[0038] In summary, the concrete prepared in this embodiment has good mechanical properties and frost resistance.

[0039] Example 2

[0040] The difference between this embodiment and embodiment 1 is that the medium sand in step 3 is 255 parts and the waste stone powder is 140 parts.

[0041] The concrete prepared in this embodiment was placed in test molds of 150mm×150mm×150mm and 100mm×100mm×400mm, compacted by tamping, and demolded after hardening and setting to obtain concrete specimens. After testing, the 7d compressive strength of the 150mm×150mm×150mm concrete specimen was 26.4MPa, and the 28d compressive strength was 42.5MPa. A freeze-thaw cycle test was performed on the 28d 100mm×100mm×400mm concrete specimen. When the number of cycles reached 200, its relative dynamic elastic modulus did not decrease to 60% of the relative dynamic elastic modulus of the blank control group (the 28d 100mm×100mm×400mm concrete specimen that was not subjected to the freeze-thaw cycle test), and the mass loss rate was less than 5%.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the medium sand in step 3 is 265 parts and the waste stone powder is 130 parts.

[0044] The concrete prepared in this embodiment was placed in test molds of 150mm×150mm×150mm and 100mm×100mm×400mm, compacted by tamping, and demolded after hardening and setting to obtain concrete specimens. After testing, the 7d compressive strength of the 150mm×150mm×150mm concrete specimen was 26.9MPa, and the 28d compressive strength was 43.0MPa. A freeze-thaw cycle test was performed on the 28d 100mm×100mm×400mm concrete specimen. When the number of cycles reached 200, its relative dynamic elastic modulus did not decrease to 60% of the relative dynamic elastic modulus of the blank control group (the 28d 100mm×100mm×400mm concrete specimen that was not subjected to the freeze-thaw cycle test), and the mass loss rate was less than 5%.

[0045] In summary, the concrete prepared in this embodiment has good mechanical properties and frost resistance.

[0046] Example 4

[0047] The concrete of this embodiment includes the following components in parts by weight: 63 parts of fly ash, 140 parts of cement, 5 parts of polycarboxylic acid high-performance water-reducing agent, 130 parts of modified waste stone powder, 265 parts of medium sand, 520 parts of crushed stone, 73 parts of water, and 0.09 parts of composite air-entraining agent.

[0048] The method for preparing concrete in this embodiment comprises the following steps:

[0049] Step 1, 70 parts of rosin powder with a particle size of 0.6 mm, 12 parts of sulfuric acid and 15 parts of bisphenol are put into a reaction kettle, and stirred at 60° C. for 4 hours to obtain a mixture; the mass concentration of the sulfuric acid is 30%;

[0050] Step 2: Add 15 parts of NaOH solution to the mixture obtained in step 1, stir at 80° C. for 3 hours, and then pour into a container to obtain a composite air-entraining agent;

[0051] Step 3, after drying the waste stone powder, place it in an alcohol solution for ultrasonic dispersion for more than 2 hours to obtain a suspension; add silane coupling agent KH-570 to a mixed solution of anhydrous ethanol and oxalic acid, stir, pour it into the suspension, stir at 75°C and then centrifuge, dry at 35°C to obtain modified waste stone powder; then mix 130 parts of modified waste stone powder, 265 parts of medium sand, and 520 parts of crushed stone to obtain a mixed aggregate; the volume ratio of anhydrous ethanol to oxalic acid in the mixed solution is 1:1, the fineness modulus of the medium sand is 2.6, and the particle size of the crushed stone is 5mm to 25mm;

[0052] Step 4: Add 63 parts of fly ash, 140 parts of cement, 5 parts of polycarboxylic acid high-performance water-reducing agent, 73 parts of water, and 0.09 parts of the composite air-entraining agent obtained in step 2 to the mixed aggregate obtained in step 3, and stir for 3 minutes at a speed of 55 r / min to obtain concrete; the fly ash particle size is 1.0 mm to 3.0 mm, and the water reduction rate of the polycarboxylic acid high-performance water-reducing agent is 23%.

[0053] The concrete prepared in this embodiment was placed in test molds of 150mm×150mm×150mm and 100mm×100mm×400mm, compacted by tamping, and demolded after hardening and setting to obtain concrete specimens. After testing, the 7d compressive strength of the 150mm×150mm×150mm concrete specimen was 28.0MPa, and the 28d compressive strength was 43.8MPa. A freeze-thaw cycle test was performed on the 28d 100mm×100mm×400mm concrete specimen. When the number of cycles reached 200, its relative dynamic elastic modulus did not decrease to 60% of the relative dynamic elastic modulus of the blank control group (the 28d 100mm×100mm×400mm concrete specimen that was not subjected to the freeze-thaw cycle test), and the mass loss rate was less than 5%.

[0054] Example 5

[0055] The concrete of this embodiment includes the following components in parts by weight: 84 parts of fly ash, 133 parts of cement, 4.8 parts of polycarboxylic acid high-performance water-reducing agent, 149 parts of modified waste stone powder, 235 parts of medium sand, 510 parts of crushed stone, 79 parts of water, and 0.1 parts of composite air-entraining agent.

[0056] The method for preparing concrete in this embodiment comprises the following steps:

[0057] Step 1, 50 parts of rosin powder with a particle size of 0.6 mm, 5 parts of sulfuric acid and 4 parts of bisphenol are put into a reaction kettle, and stirred at 60° C. for 4 hours to obtain a mixture; the mass concentration of the sulfuric acid is 30%;

[0058] Step 2: Add 12 parts of NaOH solution to the mixture obtained in step 1, stir at 80° C. for 3 hours, and then pour into a container to obtain a composite air-entraining agent;

[0059] Step 3, after drying the waste stone powder, place it in an alcohol solution for ultrasonic dispersion for more than 2 hours to obtain a suspension; add silane coupling agent KH-570 to a mixed solution of anhydrous ethanol and oxalic acid, stir, pour it into the suspension, stir at 80°C, centrifuge, and dry at 40°C to obtain modified waste stone powder; then mix 149 parts of modified waste stone powder, 235 parts of medium sand, and 510 parts of crushed stone to obtain a mixed aggregate; the volume ratio of anhydrous ethanol to oxalic acid in the mixed solution is 1:1, the fineness modulus of the medium sand is 2.4, and the particle size of the crushed stone is 5mm-25mm;

[0060] Step 4: Add 84 parts of fly ash, 133 parts of cement, 4.8 parts of polycarboxylic acid high-performance water-reducing agent, 79 parts of water, and 0.1 parts of the composite air-entraining agent obtained in step 2 to the mixed aggregate obtained in step 3, and stir for 3 minutes at a speed of 55 r / min to obtain concrete; the fly ash particle size is 1.0 mm to 3.0 mm, and the water reduction rate of the polycarboxylic acid high-performance water-reducing agent is 25%.

[0061] The concrete prepared in this embodiment was loaded into test molds of 150mm×150mm×150mm and 100mm×100mm×400mm, compacted by tamping, and demolded after hardening and setting to obtain concrete specimens; after testing, the 7d compressive strength of the 150mm×150mm×150mm concrete specimen was 27.6MPa, and the 28d compressive strength was 43.0MPa; a freeze-thaw cycle test was performed on a 28d 100mm×100mm×400mm concrete specimen, and when the number of cycles reached 200, its relative dynamic elastic modulus did not decrease to 60% of the relative dynamic elastic modulus of the blank control group (a 28d 100mm×100mm×400mm concrete specimen not subjected to a freeze-thaw cycle test), and the mass loss rate was less than 5%.

[0062] In summary, the concrete prepared in this embodiment has good mechanical properties and frost resistance.

[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A waste stone powder composite fly ash concrete suitable for high-cold areas, characterized in that: The concrete comprises the following components in parts by weight: 63-85 parts of fly ash, 120-140 parts of cement, 3.9-5.0 parts of polycarboxylic acid high-performance water reducing agent, 130-150 parts of waste stone powder, 235-265 parts of medium sand, 510-520 parts of crushed stone, 73-79 parts of water and 0.08-0.1 parts of composite air entraining agent.

2. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The composite air entraining agent comprises the following components in parts by weight: 5-12 parts of sulfuric acid, 50-70 parts of rosin powder, 4-15 parts of bisphenol, and 10-15 parts of sodium hydroxide. The mass concentration of the sulfuric acid is 20%-40%.

3. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 2, characterized in that: The method for preparing the concrete comprises the following steps: Step 1: Put rosin powder with a particle size of no more than 0.4 mm, sulfuric acid and bisphenol into a reaction kettle, and stir at 60° C. to 80° C. for more than 4 hours to obtain a mixture; Step 2: Place the NaOH solution in the mixture obtained in step 1, stir at 80° C. to 90° C. for 3 hours, and then pour the mixture into a container to obtain a composite air-entraining agent; Step 3: Weigh the waste stone powder, medium sand and crushed stone according to the mix ratio and mix them evenly to obtain mixed aggregate; Step 4: Weigh fly ash, cement, polycarboxylic acid high-performance water-reducing agent, water and the composite air-entraining agent obtained in step 2 according to the mix ratio, and then add them to the mixed aggregate obtained in step 3 and stir to obtain concrete.

4. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The fineness modulus of the waste stone powder is 2.0-2.5, and the methylene blue of the waste stone powder is less than 1.

3.

5. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The waste stone powder includes modified waste stone powder. The preparation method of the modified waste stone powder is as follows: the waste stone powder is dried and placed in an alcohol solution for ultrasonic dispersion for more than 2 hours to obtain a suspension; the silane coupling agent KH-570 is added to a mixed solution of anhydrous ethanol and oxalic acid and stirred, and then poured into the suspension, stirred at 75°C to 80°C, centrifuged, and dried to obtain the modified waste stone powder.

6. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 5, characterized in that: The volume ratio of anhydrous ethanol to oxalic acid in the mixed solution is 1:

1.

7. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The water reduction rate of the polycarboxylic acid high-performance water-reducing agent is 20% to 25%.

8. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The particle size of the fly ash is 1.0 mm to 3.0 mm.

9. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The fineness modulus of the medium sand is 2.4 to 2.

7.

10. The waste stone powder composite fly ash concrete suitable for high-cold areas according to claim 1, characterized in that: The particle size of the crushed stone is 5 mm to 25 mm.